EFFECT OF USING FERMENTED LIME PEEL WASTE (citrus aurantifolia) ON THE SIZE OF THE DIGESTIVE TRACT OF BROILER CHICKENS - Shihah, Hanna Dzawish; Sunarti, Dwi; Sumarsih, Sri; Sarjana, Teysar Adi; Suprijatna, Edjeng; Mahfudz, Luthfi Djauhari; Kismiati, Sri; Muryani, Rina; Ma’rifah, Binti; Wahyuni, Nur Maulida (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
This study examines the effect of fermented lime peel waste flour (FLPWF) on the digestive tract dimensions of broiler chickens. The materials used include 200 female Lohmann MB 202 broilers aged 14 days, with an average body weight of 379.73 ± 18.72 g. The feed ingredients include yellow corn, soybean meal, fish meal, rice bran, fermented lime peel waste flour, soybean oil, premix, CaCO3, D-L Methionine, and L-Lysine. The study was designed using a completely randomized design (CRD) with four levels of fermented lime peel waste flour (FLPWF) usage: 0%, 1%, 2%, and 3% in the ration. Each treatment was repeated five times. Data were analyzed for variance using the SPSS 19.0 software. The results showed that the use of FLPWF did not significantly affect the weight and length of the small intestine, as well as the weight-to-length ratio of the small intestine among treatments (P> 0.05). This study concludes that using fermented lime peel waste flour in rations at 1% to 3% does not reduce the relative weight, length, and weight: length ratio of the small intestine of broiler chickens. Keywords: Broiler, Fermented Lime Peel Waste Flour, Small Intestine